P63 and Ki-67 expression in trophoblastic disease and spontaneous abortion - Erfanian, Minoo (Medknow Publications Pvt Ltd, 2009)
BACKGROUND: Despite well-described histopathologic criteria, the distinction of spontaneous abortion from hydatidiform mole and complete hydatidiform mole from partial hydatidiform mole remains a problem because of interobserver and intraobserver variability. The aim of this study was to evaluate the value of two immunohistochemical markers in the differential diagnosis of subgroups of lesions of villous trophoblasts and spontaneous abortions. METHODS: Immunohistochemistry with the P63 and Ki-67 antibody was performed in formalin-fixed paraffinembedded samples of non hydropic abortion (n = 14), partial hydatidiform mole (n = 12), complete hydatidiform mole (n = 12) and choriocarcinoma (n = 12). The Ki-67 and P63 labeling index (number of positive nuclei/total number of nuclei) for villous stromal cells, cytotrophoblasts and syncytiotrophoblasts were evaluated separately by counting 100 cells of each population. Statistical analysis was carried out by χ(2) analysis, and the Mann-Whitney U test. Statistical significance was determined at p < 0.05 on the basis of 2-tailed tests. RESULTS: None of nonhydropic spontaneous abortions analyzed exhibited positive cytotrotrophoblastic and syncytiotrophoblastic cells for P63. The syncytiotrophoblastic cells were negative for p63 in all of choriocarcinomas. All of choriocarcinomas analyzed exhibited severe expression of Ki-67 in cytotrotrophoblastic cells. None of abortions and partial moles was diffusely labeled with Ki-67. CONCLUSIONS: Ki-67 labeling index in cytotrophoblastic cells is the best index to differentiate between abortion and subgroups of lesions of villous trophoblasts as well as between different subgroups of lesions of villous trophoblasts. Ki-67 is a better marker than P63 to attain this goal.